Entrepreneurship Education, Grit, and Entrepreneurial Intentions of College Students: A Mediated Moderation Model - Li, Yanbin; Zhang, Yue; Jiang, Jiang; Jiang, Wen; Zhang, Feng (Frontiers of education in China, 2025)
To investigate the moderating role of grit between entrepreneurship education and entrepreneurial intentions and explore the psychological mechanism underlying these moderating effects, this study conducted a questionnaire survey of 1,002 college students. The results showed that the consistency of interest dimension of grit plays a moderating role between entrepreneurship education and entrepreneurial intentions. The positive predictive effect of entrepreneurship education on entrepreneurial intentions only exists in the college students with higher consistency of interest dimension of grit. Entrepreneurial self-efficacy serves as a mediator in the moderating effect of the consistency of interest dimension of grit. The moderating effect of the perseverance of effort dimension of grit is insignificant, while it can positively predict entrepreneurial intentions and entrepreneurial self-efficacy. The above findings indicated that entrepreneurship education can generate different effects depending on the grit level of students. Therefore, entrepreneurship education programs are suggested to be tailor made and cultivate grit to improve the effectiveness of entrepreneurship education.